Adsorption of phosphate and cadmium on iron (oxyhydr)oxides: A comparative study on ferrihydrite, goethite, and hematite - Liu, Jing; Zhu, Runliang; Ma, Lingya; Fu, Haoyang; Lin, Xiaoju; Parker, Stephen C.; Molinari, Marco (Geoderma, 2021)
•Phosphate and Cd(II) were synergistically adsorbed with molar ratios related to surface charges of minerals.•The bonding modes of phosphate in the presence and absence of Cd(II) were dependent on the structure of minerals.•The functions of different iron (oxyhydr)oxides in controlling the composition of soils should be differentiated. Iron (oxyhydr)oxides participate in a variety of geochemical processes, and hence control the cycling of elements and quality of soils. The present work provides information about the macroscopic adsorption behaviors and microscopic mechanisms of typical cations and oxyanions (i.e., cadmium and phosphate) on three omnipresent iron (oxyhydr)oxides (i.e., ferrihydrite (Fh), goethite (Gt), and hematite (Hm)) in single- and double-solute systems, which can not only help in understanding the different adsorption behaviors of iron (oxyhydr)oxides, but also be important in developing robust and accurate surface complexation models. In both adsorption systems, Fh exhibited the strongest capacity in the uptake of phosphate and cadmium, followed by Gt and Hm; specifically, the adsorbed amounts of ions by Fh were ~ 6 times higher than those by Gt and Hm. Phosphate and cadmium can be synergistically adsorbed by the minerals. In situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectra combining with the two-dimensional correlation spectroscopic (2D-COS) analysis were employed to unravel the bonding modes of phosphate on minerals. In the single-solute adsorption systems, although the primary species on Hm and Gt were similar, i.e., protonated and non-protonated bidentate phosphate complexes, more protonated complexes were found on Hm than on Gt; whereas the complexation modes of phosphate on Fh were diversified due to the complex nature of the surfaces, including monoprotonated bidentate, non-protonated bidentate, and outer-sphere complexes. The synergistic adsorption mechanisms of phosphate and cadmium on the three minerals were analogous, including electrostatic interaction, as well as the formation of phosphate-bridged ternary complexes and surface precipitation; nevertheless, the relative contributions of the mechanisms on the minerals were distinct: electrostatic attraction was the predominant co-adsorption mechanism for ions on Gt, while surface precipitation was the most significant on Fh among the three minerals. This study can be enlightening to understand the interaction between the soil constituents, which is crucial to evaluate the fate and transport of the environmentally important substances in different geological settings.